Extreme temperature and extreme violence: evidence from Russia - Vladimir Otrachshenko; Olga Popova; José Tavares (Economic Inquiry, 2020)
We study the relationship between extreme temperatures and violent mortality, employing novel regional panel data from Russia. We find that extremely hot temperatures increase violent mortality, while extremely cold temperatures have no effect. The impact of hot temperature on violence is unequal across gender and age groups, rises noticeably during weekends, and leads to considerable social costs. Our findings also suggest that better job opportunities and lower vodka consumption may decrease this impact. The results underscore that economic policies need to target vulnerable population groups to mitigate the adverse impact of extreme temperatures. (JEL Q54, I14, K42)
Keywords: 330